Peran Asesmen Berbasis Karakter Kemandirian dalam Meningkatkan Kemampuan Pemecahan Masalah pada Siswa Sekolah Dasar - Barokah, Novita; Siti Mumun Muniroh (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the role of character-based assessment of independence in improving problem-solving skills in elementary school students. Character-based assessment of independence assesses students' learning process, not just academic results, with a focus on developing values of independence such as responsibility, initiative, and self-management skills. Through this approach, students are trained to face challenges independently, manage time, and find solutions creatively. Literature review shows a positive relationship between the level of student independence and increased problem-solving skills. However, the implementation of this assessment faces challenges such as lack of teacher understanding, time constraints, and system support. Nevertheless, character-based assessment of independence remains relevant and needs to be implemented more widely with training support for teachers, the use of technology in assessment, and synergy between schools, parents, and communities. The results of this study suggest that independence assessment should be an integral part of learning practices to create a generation of independent and solution-oriented learners.